2021
DOI: 10.1021/acsinfecdis.0c00860
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Inactivation of Prions Is Altered by Binding to the Soil Mineral Montmorillonite

Abstract: Environmental routes of transmission contribute to the spread of the prion diseases chronic wasting disease of deer and elk and scrapie of sheep and goats. Prions can persist in soils and other environmental matrices and remain infectious for years. Prions bind avidly to the common soil mineral montmorillonite, and such binding can dramatically increase oral disease transmission. Decontamination of soil in captive facilities and natural habitats requires inactivation agents that are effective when prions are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Therefore, to predict the fate of prions in soils, it is important to analyze soil properties [ 36 ]. Prion persistence in soil is a dynamic balance between protective microenvironments, such as binding to minerals, which favor prion stability [ 37 , 38 ] versus processes leading to their degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to predict the fate of prions in soils, it is important to analyze soil properties [ 36 ]. Prion persistence in soil is a dynamic balance between protective microenvironments, such as binding to minerals, which favor prion stability [ 37 , 38 ] versus processes leading to their degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Afterall, the other three candidate algorithms performed similarly with these data (see Table S2 in the Supplement), and their results hinged on entirely different sets and ranks of factor importances. Specifically, the RF algorithm ranked hunter harvest (a proxy for deer density) 36 , clay-based soils 37 41 , forest cover 13 , and then distance to streams 35 as the most important features driving its predictions of CWD-status, in that order. The DT algorithm ranked hunter harvest 36 , distance to streams 35 , clay-based soils 37 41 and then forest cover 13 as the top features of importance driving its predictions of CWD-status, in that order.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the RF algorithm ranked hunter harvest (a proxy for deer density) 36 , clay-based soils 37 41 , forest cover 13 , and then distance to streams 35 as the most important features driving its predictions of CWD-status, in that order. The DT algorithm ranked hunter harvest 36 , distance to streams 35 , clay-based soils 37 41 and then forest cover 13 as the top features of importance driving its predictions of CWD-status, in that order. And finally, the GB algorithm ranked hunter harvest 36 , distance to streams 35 , forest cover 13 , and then clay-based soils 37 41 as the top features driving its predictions of CWD-status, in that order.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic wasting disease persistence was negatively correlated with clay soil constituents, a relationship previously identified in northern Illinois, USA (Dorak et al 2017). Kuznetsova et al (2020) reported that prions readily bind to clay particles and become increasingly more difficult to extract over time but remain infectious, and others have indicated that clay‐bound prions increase the transmissibility of CWD (Booth et al 2021). Based on these relationships, we might expect that increasing clay content would result in a higher likelihood of CWD persistence, but this was not supported by our study or Dorak et al (2017).…”
Section: Discussionmentioning
confidence: 99%